2021
DOI: 10.1186/s12875-021-01383-2
|View full text |Cite
|
Sign up to set email alerts
|

Body size perception, knowledge about obesity and factors associated with lifestyle change among patients, health care professionals and public health experts

Abstract: Background The attitudes towards obesity may have an important role on healthier behavior. The goal of the present study was to explore the attitudes towards obesity and to investigate how these attitudes were associated with lifestyle-changing behavior among the patients attending primary care centers, health care professionals and public health experts. Methods This cross-sectional survey study was performed in 10 primary care offices in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Grading a patient's obesity level is an important activity in healthcare 1 . Obesity acts as a risk factor for various diseases, including chronic diseases, type-2 diabetes, heart disease, and certain cancers [2][3][4][5][6][7] .…”
mentioning
confidence: 99%
“…Grading a patient's obesity level is an important activity in healthcare 1 . Obesity acts as a risk factor for various diseases, including chronic diseases, type-2 diabetes, heart disease, and certain cancers [2][3][4][5][6][7] .…”
mentioning
confidence: 99%
“…A previous Saudi study assessed the attitudes of adults toward obesity and showed that age, education level, and BMI were determinants for attitudes toward obesity [23] similar to our study. Age also significantly affected lifestyle-changing behavior, with younger people being more likely to change their lifestyle, as reported by Zelenyte et al [15]. The willingness to lose weight was reported to be affected by BMI and gender, i.e., obese participants, especially men, showed a willingness to reduce weight more than men and women who are overweight [24].…”
Section: Discussionmentioning
confidence: 62%
“…Most reported that obesity is caused by a single cause. In a similar study done in Lithuania, almost two-thirds of 198 people with obesity were either unhappy or very unhappy with their current weight [ 15 ]. This attitude about obesity and the perception of it as a disease is encouraging because it forms a good basis for healthcare providers to initiate obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…Robert Crawford has pointed out that in recent decades in Western societies, there has been heightened concern about health issues from an individualistic perspective, resulting in consumers' repeated attempts to regulate their lifestyles [53]. As regards obesity, individual-centred explanations have been reported among people taking part in lifestyle change interventions [54] among health care professionals [55] and among children [56].…”
Section: Discussionmentioning
confidence: 99%